COVID-19 era-related e-learning: a cross-sectional web-scale study of cyberchondria, internet addiction and anxiety-related symptomatology among university nursing students - Majd T Mrayyan; Abdullah Algunmeeyn; Hamzeh Y Abunab; Imad Alfayoumi; Ja'far M Alkhawaldeh; W A Suliman; Mohammad Abu Hasheesh; Raed Shudifat (BMJ Open, 2023)
Objective The study assessed COVID-19 era-related e-learning cyberchondria, internet addiction and anxiety-related symptomatology among nursing students. The relationships, predictors and differences between the studied concepts were measured.Design In 2021, a quantitative cross‐sectional research design using a web survey with a sample size of 333 nursing students yielded a response rate of 70%.Results Nursing students had a moderate level of cyberchondria, low to moderate internet addiction, a moderate to severe level of anxiety and depression, and a normal stress level. Demographic characteristics, cyberchondria, internet addiction and anxiety-related symptomatology were significantly correlated. Grade point average, age, type of organisation where the students were trained and level of education were significant predictors of the studied variables. Significant differences in the studied concepts were found based on the sample’s characteristics such as gender, type of organisations or universities where the students were trained or studied, and age.Conclusion Cyberchondria, internet addiction, depression, anxiety and stress symptomatology are troublesome. Higher education organisations might benefit from examining the variables of interest and investigating the relations between internet addiction and depression and anxiety symptomatology among nursing students. Such research will aid in tailoring treatments to assist vulnerable students by targeting counselling and educational efforts toward building a future generation of nurses with reduced cyberchondria, internet addiction and anxiety-related symptomatology.